A randomised double-blind placebo-controlled study of zinc lozenges for the prevention of post-operative sore throat in patients undergoing surgery under general anaesthesia with endotracheal intubation - Sparsha S. Vasisht; Shyamsunder Kamath; Siddesh N. Kadur (Journal of Clinical and Scientific Research)
Background: Post-operative sore throat (POST) is a frequent complication that follows elective surgeries under general anaesthesia with endotracheal (ET) intubation. Methods: A double-blind randomised placebo-controlled study was conducted from March 2021 to January 2023. One hundred patients aged 18–60 years, belonging to the American Society of Anaesthesiologists I/II and Mallampati class I/II; undergoing elective surgeries (duration 1–4 h) under general anaesthesia with ET intubation were studied. The patients were randomised to receive zinc lozenges (Group Z) or placebo (Group P) for the prevention of POST. Incidence and severity of POST was evaluated at 30 min, 2 h, 4 h and 24 h after-surgery. Results: Compared to Group P, Group Z had lower occurrence of POST (16% Vs 44%, P = 0.002); specifically at time intervals of 2 h (4% Vs 20%, P = 0.028), 4 h (12% Vs 34%, P = 0.009) and 24 h (14% Vs 42%, P = 0.002). The distribution of overall severity of POST was similar between Group Z and Group P (mild POST 87.5% Vs 59.1%, respectively; moderate POST 12.5% vs. 31.8% respectively; and severe POST 0% vs. 9.1%, respectively) (P = 0.518). Conclusions: The pre-operative use of zinc lozenge shows effective prevention in POST incidence and severity during the follow-up period of 24 h after surgery. Clinical trial registration: Clinical Trials Registry-India; No.: CTRI/2022 / 01/039682; URL: https://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=NTQwODc=&Enc=&userName=CTRI/2022/01/039682.